Heterogeneity of presynaptic proteins: do not forget isoforms - Bragina, Luca; Fattorini, Giorgia; Giovedì, Silvia; Bosco, Federica; Benfenati, Fabio; Conti, Fiorenzo (Frontiers in Cellular Neuroscience, 2013)
Analysis of presynaptic protein expression in glutamatergic and GABAergic central synapses performed in several laboratories and with different techniques is unveiling a complex scenario, largely because each presynaptic protein exists in several isoforms. The interpretation of these findings is generally based on the notion that each synapse and each synaptic vesicle contains one of the isoforms of each family of presynaptic proteins. We verified whether this interpretation is tenable by performing triple labeling and immunoisolation studies with the aim of detecting two isoforms of a given presynaptic protein in glutamatergic or GABAergic axon terminals and/or synaptic vesicles. Here, we show that: 1) the possibility that not all families of presynaptic proteins are expressed in all terminals must be taken into serious account; 2) the expression of a given protein isoform in a terminal does not exclude the expression of other isoforms of the same protein in the same terminal and in the same vesicle. These conclusions open new and interesting problems; their experimental analysis might improve our understanding of the physiology and patophysiology of central synapses.